SIMULASI DAMPAK PEMULIHAN SEKTOR PARIWISATA PASCA PANDEMI COVID-19 TERHADAP PEREKONOMIAN BALI - Sotya Fevriera; Bagas Kusuma Tjandra (Bina Ekonomi, 2023)
During the Covid-19 pandemic, Indonesian government prohibited foreign tourist to enter Indonesia. It hit Bali’s economics. As the condition improved, the Ministry of Tourism and Creative Economy (MoTCE) is targeting an increase in number of tourist in Bali. This research among others aims to simulate MoTCE’s target on Bali’s economic output and employment. Data used in this research are Bali’s input output table of 17 industrial origins in 2016, survey of tourist length of stay and expenditure in Bali in 2019, and number of tourist in Bali in 2021. The analysis method employed to achieve the goal is multiplier effect analysis on output and employment. The simulation results show, besides the Accommodation, Food and Drink Provision sector, 3 sectors with the highest impact of percentage increase, both for output and employment, are: (1) the Energy and Waste Processing sector; (2) Agriculture, Forestry, and Fisheries sector; and (3) Wholesale and Retail Trade, Car and Motorcycle Repair sector.